Process enhancement at near neutral pH of a homogeneous photo-Fenton reaction using ferricarboxylate complexes: Application to oxytetracycline degradation - João H. O. S. Pereira (2014)
This work demonstrates the application at near neutral pH of a photo-Fenton reaction mediated by ferricarboxylates on the treatment of aqueous solutions containing the antibiotic Oxytetracycline (OTC) under solar irradiation. The formation of a Fe:OTC complex after Fe2+ oxidation to Fe3+, in the presence of H2O2, showed the inconvenience of using the conventional Fe2+/H2O2/UV-Vis process at near neutral pH levels, as the complex is retained in the filter. To overcome this, a Fe3+/Oxalate/UV-Vis or Fe3+/Citrate/H2O2/UV-Vis process was proposed. The higher tendency of Fe3+ to form complexes with carboxylates avoids the formation of Fe:OTC complexes and allows for proper OTC detection along reaction times. The photo-Fenton process itself is improved by the extension of the iron solubility to higher and more practical pH values, by the increase of the quantum yield of Fe2+ production and by presenting stronger radiation absorption at wavelengths up to 580 nm. In this way, process efficiency was evaluated for different variables such as Fe3+ concentration, pH, temperature and irradiance, using a compound parabolic collector (CPC) photoreactor at lab-scale under simulated solar radiation. Reaction rates were compared in the presence of different inorganic anions and humic acids, and in two different real wastewater matrixes. Results obtained in a CPC pilot-scale plant under natural solar light, using an iron/oxalate molar ratio